Aroma-loaded microcapsules with antibacterial activity for eco-friendly textile application: synthesis, characterization, release, and green grafting - Sharkawy, Asma (2017)
Fragrant and antimicrobial properties were conferred to cotton fabrics following microencapsulation using green materials. Limonene and vanillin microcapsules were produced by complex coacervation using chitosan/gum Arabic as shell materials and tannic acid as hardening agent. The effect of two emulsifiers; Span 85 and polyglycerol polyricinoleate (PGPR), on the encapsulation efficiency (EE%), microcapsule’s size and morphology, and cumulative release profiles was studied. The mean diameter of the produced microcapsules ranged between 10.4 and 39.0 μm, whereas EE% was found to be between 90.4% and 100%. The use of Span 85 resulted in mononuclear morphology while PGPR gave rise to polynuclear structures, regardless of the core material (vanillin or limonene). The obtained microcapsules demonstrated a sustained release pattern; namely the total cumulative release of the active agents after 7 days at 37 ± 1 °C was 75%, 52% and 19.4% for the polynuclear limonene microcapsules, the mononuclear limonene microcapsules and the polynuclear vanillin microcapsules, respectively. Grafting of the produced microcapsules onto cotton fabrics through na esterification reaction using citric acid as a nontoxic cross-linker followed by thermofixation and curing, was confirmed by SEM and FTIR spectroscopy. Standard antibacterial assays conducted on both microcapsules alone and impregnated onto the fabrics indicated a sustained antibacterial activity.